2011
DOI: 10.1007/s11259-011-9462-1
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus uberis-specific T cells are present in mammary gland secretions of cows and can be activated to kill S. uberis

Abstract: The presence, phenotype and function of Streptococcus uberis-specific T cells in the mammary gland secretion (MGS) and blood of cows exposed to S. uberis were assessed. MGS T cells in the udder were purified and incubated with autologous blood monocytes as antigen-presenting cells (APC). Most cows, irrespective of prior S. uberis infection status and lactation status, were shown to have S. uberis-specific T cells both in MGS and in the blood. When cells from a subgroup of cows were studied, it was found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
(49 reference statements)
0
30
0
1
Order By: Relevance
“…Vaccination with S. uberis enhances the proliferative response of peripheral blood lymphocytes to S. uberis antigens and induces an antigen-specific cytotoxic effect against blood monocytes/macrophages that have phagocytosed S. uberis (Hill et al, 1994;Wedlock et al, 2014). It is hoped that better understanding or manipulation of the cellular immune response to S. uberis may contribute to successful vaccine development (Denis et al, 2011;Schukken et al, 2011b), but it remains a challenge to activate and harness the cell-mediated arm of the immune response in the unique immunological environment of the mammary gland (Bharathan & Mullarky, 2011).…”
Section: Vaccinationmentioning
confidence: 99%
“…Vaccination with S. uberis enhances the proliferative response of peripheral blood lymphocytes to S. uberis antigens and induces an antigen-specific cytotoxic effect against blood monocytes/macrophages that have phagocytosed S. uberis (Hill et al, 1994;Wedlock et al, 2014). It is hoped that better understanding or manipulation of the cellular immune response to S. uberis may contribute to successful vaccine development (Denis et al, 2011;Schukken et al, 2011b), but it remains a challenge to activate and harness the cell-mediated arm of the immune response in the unique immunological environment of the mammary gland (Bharathan & Mullarky, 2011).…”
Section: Vaccinationmentioning
confidence: 99%
“…Sortase-anchored proteins derived from S uberis may be potential candidates for vaccine as they are important potential virulence antigens contributing to the pathogenesis of bovine mastitis [184]. Recently, Denis et al [185] reported that cows which developed mastitis after environmental exposure to S uberis developed bactericidal antibodies and T cells in blood and milk, resulting in an increased level of interferon-gamma (IFN-γ) that was specific for in-vitro killing of S uberis [185]. Clearly, research on the development of an effective vaccine against S uberis -associated mastitis is highly warranted.…”
Section: Vaccines Against Streptococcus Uberismentioning
confidence: 99%
“…On sait que ces lymphocytes présentent un phénotype qui les fait qualifier de cellules mémoires (Taylor et al, 1994). Quelques travaux indiquent que les lymphocytes T CD8+ peuvent avoir une activité antibactérienne (Denis et al, 2011), mais aussi qu'ils peuvent avoir une activité immunosuppressive sur les fonctions des lymphocytes T CD4+ (Shafer-Weaver et Sordillo, 1997). Les fonctionnalités des lymphocytes T auxiliaires CD4+ que l'on trouve dans le lait n'ont pas été caractérisées.…”
Section: Les Lymphocytes Et Les Macrophages Du Lait Et La Notion De Cunclassified